Opposite Enantioselectivity by Nanotubes and Nanospheres Self‐Assembled from Dirhodium(II) and an l‐Glutamic Acid Terminated Bolaamphiphile. Issue 10 (13th March 2018) - Yuan, Chenhuan; Jiang, Jian; Sun, Hui; Wang, Decai; Hu, Yonghong; Liu, Minghua
Abstract: Coordination is an important factor that can be used to modulate the structure and function of self‐assembly systems. Herein, we report the coordination‐regulated self‐assembly of chiral nanostructures and their enantioselective catalytic performances. We found that if a rhodium complex and anl ‐glutamic acid terminated bolaamphiphile were self‐assembled by coordination, single‐walled nanotubes and nanospheres could be obtained depending on the molar ratio. Interestingly, the nanotubes and nanospheres showed opposite supramolecular chirality even though the same chiral bolaamphiphile was used. If the nanospheres and nanotubes were used as catalysts for the asymmetric cyclopropanation reaction, opposite enantioselectivities were obtained, which indicated that it was the supramolecular chirality rather than the molecular chirality that controlled the enantioselectivity of the asymmetric reaction. This work provides not only a feasible method to construct different nanostructures through metal coordination but also a new pathway of transferring chirality from the supramolecular level to chiral products. Abstract : Supra ! A Rh complex and anl ‐glutamic acid terminated bolaamphiphile (HDGA) self‐assemble into nanospheres and nanotubes by changing the mixing ratio. These nanostructures show opposite supramolecular chirality, which leads to opposite enantioselectivity in the catalyzed asymmetric cyclopropanation reaction. The supramolecular chirality determines the ee values of the products, not the molecular chirality. tfa=trifluoroacetate.